HUBUNGAN POLA ASUH ORANG TUA DENGAN PERILAKU MEROKOK PADA REMAJA LAKI-LAKI DI RW 016 KELURAHAN PAMULANG TIMUR - Sondang Deri Maulina Pasaribu; Widya Gita Oktaviana (Jurnal Kesehatan STIKes IMC Bintaro, 2021)
Smoking behavior is a serious problem for Indonesia at this time, especially for adolescents, because some teenagers in Indonesia have considered that smoking is a necessity that cannot be avoided such as the need for "slang", the need to relax and various other reasons that make smoking a cigarette. common thing. So that the researchers formulated the problem of this study "the relationship between parenting style and smoking behavior in teenage boys in RW 016, Pamulang Timur Village, South Tangerang City". With the aim of knowing and analyzing the relationship between parenting styles and smoking behavior in male adolescents in RW 016, Pamulang Timur Village, South Tangerang City. The research design was Case Control, conducted on 48 male adolescents who were recruited by Quota Sampling. Data were collected using a questionnaire and analyzed by Chi-Square. As a result, most of the parents have democratic parenting (29; (60.4%)) and the number of respondents who smoke and do not smoke is the same (50% vs 50%). The results showed that there was a relationship between parenting styles and smoking behavior in male adolescents (P = 0.000, OR = 14.0). It is recommended that community nurses provide counseling or provide regular and ongoing education to adolescents and teenage parents about smoking and the dangers it causes.